First-Principles Point Defect Models for Zr7Ni10 and Zr2Ni7 Phases - Diana F. Wong; Kwo-Hsiung Young; Taihei Ouchi; K. Y. Simon Ng (Batteries, 2016)
Synergetic effects in multi-phased AB2 Laves-phase-based metal hydride (MH) alloys enable the access of high hydrogen storage secondary phases, despite the lower absorption/desorption kinetics found in nickel/metal hydride (Ni/MH) batteries. Alloy design strategies to further tune the electrochemical properties of these secondary phases include the use of additives and processing techniques to manipulate the chemical nature and the microstructure of these materials. It is also of particular interest to observe the engineering of constitutional point defects and how they may affect electrochemical properties and performance. The Zr7Ni10 phase appears particularly prone to point defects, and we use density functional theory (DFT) calculations coupled with a statistical mechanics model to study the theoretical point defects. The Zr2Ni7 phase appears less prone to point defects, and we use the Zr2Ni7 point defect model, as well as experimental lattice parameters, with Zr7Ni10 phases from X-ray diffraction (XRD) as points of comparison. The point defect models indicate that anti-site defects tend to form in the Zr7Ni10 phase, and that these defects form more easily in the Zr7Ni10 phase than the Zr2Ni7 phase, as expected.